Penerapan Lima Prinsip Dasar Pesantren Tebuireng dalam Membentuk Karakter Santri di Pesantren Tebuireng Jombang - Isnan Badarudin Kamal (Pascasarjana IAI Nasional Laa Roiba Bogor, 2024)
The Five Basic Principles of the Tebuireng Islamic Boarding School is the main motto used by the Tebuireng Islamic Boarding School in implementing the character of its students. These five characters are a summary of the seventh supervisor of the Tebuireng Islamic Boarding School (KH. Salahuddin Wahid) which he took from one of the books written by Hadratus Shaykh KH. Muhammad Hasyim Asy;ari, namely in the book